Coping with failures: how emotions, individual traits, expectation-importance and prior experience affect reactions to violated achievement expectations - Orphal, Lara; Pinquart, Martin (Frontiers in Psychology, 2025)
BackgroundAccording to the model ViolEx 2.0, individuals cope with expectation violations in three different ways: assimilation (increasing efforts for expectation maintenance), immunization (ignoring or downplaying discrepant information) and accommodation (changing the expectation). Which contextual and personality factors influence expectation maintenance and change is still subject to investigation.ObjectiveThis study aimed to determine how two academic emotions, confusion (an epistemic emotion) and annoyance (an achievement emotion), as well as Tolerance of Ambiguity (as personality factor), the importance of an expectation and the prior experiences regarding this expectation (situational factors), relate to coping with expectation violations in achievement contexts.MethodsVignettes describing achievement expectation violations were presented to an initial sample of 310 participants. The stories varied in importance of an achievement (high, low), prior experience (confirming, disconfirming, no prior experience), and emotional reaction to the achievement failure (confusion, annoyance, no emotional reaction). As outcome measures, participants indicated their subjective likelihood of using three different coping responses to the expectation violation: assimilation, immunization and accommodation. In addition, Tolerance of Ambiguity was assessed using the German version of the Tolerance of Ambiguity Scale.ResultsOverall, annoyance and confusion predicted higher assimilation and lower immunization. Higher Tolerance of Ambiguity predicted higher immunization and lower accommodation, while higher importance of an initially expected outcome resulted in higher assimilation and lower accommodation. Finally, prior expectation confirmation strengthened expectations, resulting in higher assimilation and immunization, and lower accommodation, while disconfirming prior experience was taken into account only for accommodation. The tendency towards accommodation increased with age, and level of assimilation was lower in men than in women.ConclusionWhen trying to stabilize expectations, it is most helpful to frame communication around importance and confirming evidence. The effect of confirming evidence is much greater than that of disconfirming evidence. While two academic emotions, namely confusion and annoyance, increase the intentions to exert efforts and decrease the likelihood of immunization, their effect is also much smaller than the effect of importance. Finally, we conclude that older individuals accommodate more, and higher Tolerance of Ambiguity makes it more likely to maintain expectations despite discrepancies.